Fostering the basis of Computational Thinking in preschool and early Primary Education through building blocks - Raimundo da Silva Soares Junior; Eneyse Dayane Pinheiro; Cristiane Maria Sato; Amanda Yumi Ambriola Oku; João Ricardo Sato (Academic Bright Collaboration, 2026)
Purpose – Computational Thinking (CT) is recognized as an essential competence for the 21st century, yet introducing CT in preschool and early primary education is challenging because young children rely heavily on concrete reasoning and are still developing literacy skills. This study aims to propose a neuroscience-informed conceptual framework that uses building block (BB) activities as a developmentally appropriate pathway to foster early CT skills. The framework integrates principles from cognitive neuroscience, embodied cognition, and computer science education to support abstraction, decomposition, pattern recognition, and algorithmic reasoning. Methods – This study employs a conceptual research design based on an integrative theoretical synthesis. The framework was developed through a critical review of interdisciplinary literature in computational thinking, educational neuroscience, developmental psychology, and embodied learning. Building block activities were selected and structured according to three pedagogical criteria: cognitive alignment with executive functions, developmentally appropriate scaffolding for children aged 4–9, and accessibility using non-electronic materials. Findings – The study proposes a pedagogical framework consisting of several building block activities, including free play construction, illustrated tutorials, multi-perspective template building, unplugged programming, debugging exercises, constraint-based construction, and engineering challenges. These activities support core CT practices such as decomposition, algorithm design, pattern recognition, and debugging, while also strengthening creativity, spatial cognition, and collaborative problem-solving. Research implications – As a conceptual study, the framework has not yet been empirically validated and therefore its effectiveness requires further testing through classroom experiments and large-scale educational interventions.Originality –This study contributes a novel synthesis that connects neuroscience, embodied learning, and computational thinking pedagogy into a coherent framework for early education, providing practical guidance for introducing CT concepts without relying on digital technologies.